Upstream Advanced C1. Student's Book - Evans V.; Evans V.; Edwards L.; Dooley J. (Newbury Express Publishing, 2008)
Upstream Advanced C1 is a modular secondary-level course for learners of the English language at CEF C1 level. The series combines active English learning with a variety of lively topics presented in themed units.
Keywords: 811.111